Modulation of Host-Pathogen Communication by Extracellular Vesicles (EVs) of the Protozoan Parasite Leishmania - Dong, George; Filho, Alonso Lira; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmania genus protozoan parasites have developed various strategies to overcome host cell protective mechanisms favouring their survival and propagation. Recent findings in the field propose a new player in this infectious strategy, the Leishmania exosomes. Exosomes are eukaryotic extracellular vesicles essential to cell communication in various biological contexts. In fact, there have been an increasing number of reports over the last 10 years regarding the role of protozoan parasite exosomes, Leishmania exosomes included, in their capacity to favour infection and propagation within their hosts. In this review, we will discuss the latest findings regarding Leishmania exosome function during infectious conditions with a strong focus on Leishmania-host interaction from a mammalian perspective. We also compare the immunomodulatory properties of Leishmania exosomes to other parasite exosomes, demonstrating the conserved, important role that exosomes play during parasite infection.